Evaluation of the Diagnostic Accuracy of the CareStart™ Glucose-6-Phosphate Dehydrogenase Deficiency Rapid Diagnostic Test among Chinese Newborns. (10th February 2020) - Yu, Fengting; Zhang, Sufen; Chen, Binhuan; Zhou, Yuqiu; Ma, Chengjie; Yang, Siyuan; Tang, Yunxia; Huang, Dan; Xie, Xiaohui; Xiao, Qizhi; Wang, Linghang
Abstract: Previous studies have shown that the CareStart™ G6PD Deficiency rapid diagnostic test has high diagnostic accuracy on G6PD deficiency in Africa and Thailand, but not in China. As there are regional differences of G6PD genotype distribution, we are attending to verify the effectiveness of the kit in Chinese population. The study cohort included 247 newborns admitted to our hospital for jaundice. The quantitative detection of G6PD enzyme activity and G6PD gene mutations analysis was used to classify the status of G6PD deficiency. The performance of CareStart™ assays was verified by calculating the sensitivity, specificity and area under the receiver operating characteristic curve (AUC) based on the corrected G6PD deficiency status. In male newborns, the sensitivity of the CareStart™ assay was 98.9%, the specificity was 94.2% and the AUC was 0.97. In female newborns, the sensitivity was 58.5% when the cutoff value of residual enzyme activity was 100%; however, the sensitivity was 100% when the cutoff value was 60%. Therefore, the CareStart™ test can effectively screen G6PD deficiency in male newborns and female infants with less than 60% residual enzyme activity, female infants with residual enzyme activities of 60–100% are more likely to be missed diagnosed among Chinese newborns.